Examining the issue of Islam and Muslims in the media: a perspective of Malaysian media practitioners - Hassan, Fauziah; Yusoff, Sofia Hayati; Kanaker, Osama; Mustafa, Muhamad Zaki; Omar, Siti Zobidah (Human Resource Management Academic Research Society, 2020)
Researching on Islam and Muslims-related issues in the media have been a never-ending debate and always have been updated time by time. It catches the attention of academics, scholars, preachers, researchers to discuss on the alternative platform in reducing or somewhat controlling what the media should report about particularly on Islam and Muslims issues. The aim of this study is to examine the reportings related to Islam and Muslims issues of the Western newspapers. Interviews were conducted among eight Malaysian media practitioners to identify how they translate the meaning of work as a journalist in Islamic context, and also to find out their best practices in producing a balanced and fair news reporting. The interviews were later transcribed verbatimly, analyzed and deliberated their experiences towards this issue. Results show that they believe as Muslim journalists, they should be true, trusted and not bias in reporting news. Further, they also find out that having good references from experts and doing some research before reporting on any issues are very important especially in reporting news globally. Thus for them, the adaptation of good journalistic practices represent a positive image of Islam and Muslims in order to continue creating a surrounding of Islam and Muslims at present and in the future.